The Chickpea Early Flowering 1 (Efl1) Locus Is an Ortholog of Arabidopsis ELF3 . Issue 2 (17th August 2017) - Ridge, Stephen; Deokar, Amit; Lee, Robyn; Daba, Ketema; Macknight, Richard C.; Weller, James L.; Tar'an, Bunyamin
Abstract : A mutation in a gene implicated in circadian clock function is associated with early flowering in a commercially significant chickpea cultivar. Abstract: In climates that experience short growing seasons due to drought, heat, or end-of-season frost, early flowering is a highly desirable trait for chickpea ( Cicer arietinum ). In this study, we mapped, sequenced, and characterized Early flowering1 (Efl1), an ortholog of Arabidopsis ( Arabidopsis thaliana ) EARLY FLOWERING3 ( ELF3 ) that confers early flowering in chickpea. In a recombinant inbred line population derived from a cross between CDC Frontier and ICCV 96029, this gene was mapped to the site of a quantitative trait locus on Ca5 that explained 59% of flowering time variation under short days. Sequencing of ELF3 in ICCV 96029 revealed an 11-bp deletion in the first exon that was predicted to result in a premature stop codon. The effect of this mutation was tested by transgenic complementation in the Arabidopsis elf3-1 mutant, with the CDC Frontier form of CaELF3a partially complementing elf3-1 while the ICCV 96029 form had no effect on flowering time. While induction of FLOWERING LOCUS T homologs was very early in ICCV 96029, an analysis of circadian clock function failed to show any clear loss of rhythm in the expression of clock genes in ICCV 96029 grown under continuous light, suggesting redundancy with other ELF3 homologs or possibly an alternative mode of action for this gene in chickpea. The 11-bp deletion was associated with early flowering in global chickpea germplasm but was not widely distributed, indicating that this mutation arose relatively recently.